An Exploratory Study Into the Effects of Regular Cold‐Water Sea Swimming on Daily Indices of Mental Health - Jill Forsten; Mark A. Wetherell (Lifestyle Medicine)
ABSTRACT Aims There is an emerging literature demonstrating the physical and psychological benefits of cold‐water swimming. The majority of this research, however, is qualitative or assesses effects across several months. As daily changes in mood contribute to overall well‐being, the current study sought to explore more proximal changes by adopting a diary approach to investigate the effects of regular cold‐water swimming. Methods Data were collected from an opportunistic sample of healthy, regular, female swimmers (N = 13) in the United Kingdom. Participants completed online questionnaires twice daily. They reported whether it was a swim day or a non‐swim day and then completed questions assessing state, cognitive and somatic anxiety, self‐confidence (morning and evening) and feelings of wellness and sleep quality the night before (morning only). Analysis of variance was conducted to assess differences between swim and non‐swim days. Results Cold‐water swimming led to significant reductions in anxiety and increases in self‐confidence on the day of a swim and improved self‐reported sleep and lower levels of next‐morning anxiety. Conclusions This exploratory study is the first to utilise a daily diary method to capture proximal changes in regular cold‐water swimmers. These results provide further evidence of the beneficial effects of cold‐water swimming on factors that contribute to psychological well‐being.